The Path to Entrepreneurship: The Role of Social Networks in Driving Entrepreneurial Learning and Education - Wasim, Jahangir (2024)
This research aims to examine the extent to which the way entrepreneurs learn is reflected in entrepreneurship education, highlighting the existing gap between the literature on entrepreneurial learning and the practice of entrepreneurship education. To explore entrepreneurial learning in-depth, we adopted an interpretivist-constructivist approach that involves participant observation at coworking spaces and semi-structured interviews with entrepreneurs. Data were subsequently analyzed using thematic analysis. Major findings indicate that social networks play a vital role in facilitating entrepreneurial learning, with context and network serving as essential learning mechanisms. However, these elements are often disregarded in traditional entrepreneurship education approaches. This study highlights a gap in the literature where the focus of entrepreneurial learning is primarily on entrepreneurs, while entrepreneurship education primarily focuses on students and educators. The study’s contribution is its emphasis on the importance of social networks in entrepreneurial learning and its potential for redesigning entrepreneurship education. By bridging the gap between entrepreneurial learning and entrepreneurship education, it is possible to create educational approaches that more closely mimic how entrepreneurs learn in real life, potentially leading to more impactful entrepreneurial activity.